Comparative study on the infection rates of different laboratory strains of Glossina species by Trypanosoma congolense - Moloo, S.K.; Kutuza, S.B. (Wiley, 1988)
ABSTRACT. Teneral Glossina morsitans centralis Machado, G. austeni Newstead, G. palpalis palpalis Robineau‐Desvoidy, G. p. gambiensis Vanderplank, G. fuscipes fuscipes Newstead, G. tachinoides Westwood and G. brevipalpis Newstead, from laboratory‐bred colonies, were fed at the same time on the flanks of ten goats infected with Trypanosoma congolense Broden isolated in Tanzania or in Nigeria. The seven tsetse species were infected over the range 0.3–49.2%. Survival of both T. congolense isolates was best in G. m. centralis, poorest in G. austeni and the four palpalis group tsetse, with G. brevipalpis intermediate. It is suggested that there are differences in the gut of different laboratory‐bred cultures of Glossina Westwood species and subspecies such that T. congolense parasites can survive better in the gut of some than in others and undergo cyclical development to metacyclics in the hypopharynx.